Stress, Depression, Self-esteem, and Self-efficacy of Nursing Students a Higher Education Institution - Anusornteerakul, Soiy; Boonmala, Nongnuch; Harnklar, Suphaphak; Ounkaew, Anchalee; Wangtapan, Kattika (Journal of The Royal Thai Army Nurses, 2024)
This correlational descriptive research aimed to study stress levels, depression, self-esteem, and self-efficacy of nursing students, and the relationship between stress, depression, self-esteem, and self-efficacy. The sample was 73 third-year nursing students at a higher education institution, in Udon Thani Province. The research instruments were 20-item stress questionnaire, 9-item depression, 10-item self-esteem, and 10-item self-efficacy questionnaires. The questionnaires had a Cronbach alpha coefficient of .93, 87, .74, and .93 respectively. The data were analyzed using descriptive statistics and the Pearson correlation coefficient. The research results found that students had moderate to high levels of stress 17.8%, severe level of depression 1.4%, low self-esteem 24.7%, moderate self-efficacy 24.7%. The stress has a positive relationship with depression (r = .724, p<. 001). Stress and depression were negatively related to self-esteem (r = -.320, p = .01 and r = -.343, p<.01, respectively), but not related to self-efficacy. The self-esteem was positively related to self-efficacy (r = .260, p<.05). Suggestions: students who have moderate to high levels of stress, and severe levels of depression should be promoted self-esteem and self-efficacy to reduce stress and prevent depression